Nasal eosinophilia and eosinophil peroxidase in children and adolescents with rhinitis - Yeonu Choi (Korean Journal of Pediatrics, 2019)
Background Researchers have shown that eosinophil peroxidase (EPO) is a relatively accurate marker of eosinophilia and eosinophil activity. However, its use as a marker of eosinophilic inflammation in nasal secretions is limited because the diagnostic cutoff values of EPO for use as a one-time test for allergic diseases such as allergic rhinitis have not been established. Purpose To identify the correlation between nasal eosinophil count and EPO in children and adolescents with rhinitis. Methods We recruited patients <18 years of age with rhinitis for more than 2 weeks or more than 2 episodes a year whose nasal eosinophil and EPO were measured at a single allergy clinic. The eosinophil percentage was calculated by dividing the eosinophil count by the number of total cells under light microscopy at ×1,000 magnification. EPO and protein were measured from nasal secretions. We retrospectively analyzed the correlation between nasal eosinophils and protein-corrected EPO (EPO/protein) value. Results Of the 67 patients enrolled, 41 were male (61.2%); the mean age was 8.2±4.0 years. The median nasal eosinophil count was 1 and percentage was 1%. The median protein-corrected EPO value was 12.5 ng/μg (range, 0–31 ng/μg). There was a statistically significant correlation between eosinophil count and percentage (P<0.001). However, the eosinophil percentage and EPO did not correlate. The eosinophil count and EPO had a statistically significant correlation (P =0.01). The EPO cutoff value examined for nasal eosinophil counts of 2, 5, 10, and 20 was 17.57 ng/μg regardless of the reference count. The largest area under the curve value was obtained when the receiver operating characteristic curve was drawn using the eosinophil count of 2. Conclusion Nasal eosinophil count was significantly associated with protein-corrected EPO.